Phytochemical-assisted biosynthesis of silver nanoparticles from Ajuga bracteosa for biomedical applications. (24th July 2020) - Afreen, Afshan; Ahmed, Rashid; Mehboob, Saadia; Tariq, Muhammad; Alghamdi, Huda Ahmed; Zahid, Alap Ali; Ali, Imran; Malik, Kausar; Hasan, Anwarul
Abstract: Silver nanoparticles (AgNPs) synthesized from plant extracts are widely used for the cure of many diseases from fever to cancers. Keeping in view the medicinal value of AgNPs, here we report a cost-effective phytochemical method for the biosynthesis of silver nanoparticles from Ajuga bracteosa . A. bracteosa is an important medicinal plant used to cure fever, appetite-loss, and cancer. Silver-nanoparticles were prepared from the aqueous extract of the plant. The methanolic extract of A. bracteosa (ABMF) was separated and n-hexane (ABHF) and chloroform (ABCF) fractions were obtained from the methanolic crude extract. The AgNPs were characterized by UV-Visible spectrophotometer, FTIR, XRD, and TEM. The total phenolic contents (TPC) and total flavonoid contents (TFC) in different fractions were determined and compared with AgNPs. The medicinal value of ABMF, ABHF, ABCF, and AgNPs was evaluated by antibacterial, antioxidant, anti-inflammatory, and cytotoxicity bioassays. The UV-visible spectrum showed a peak at 484 nm while FTIR results suggested strong capping of phytochemicals on AgNPs which was confirmed by a high amount of TPC and TFC. XRD analysis depicted a high degree of crystallinity and smaller size of AgNPs. TEM results showed spherical shaped AgNPs of size range 50 ± 12 nm. The biosynthesized AgNPs showed better antibacterial activity than plant extract fractions. Similarly, AgNPs have shown better antioxidant, cytotoxicity against cancer cell lines in-vitro, and anti-inflammatory activity in-vivo than a plant extract. The great medicinal value of A. bracteosa might be due to the presence of pharmacologically active phytochemicals such as diterpenoids, neo-clerodane flavonol glycosides, ergosterol, iridoid glycosides, phytoecdysones, and other polyphenols. These phytochemicals surround the silver nanoparticles during green synthesis and therefore, this capping of phytochemicals over silver nanoparticles results in enhanced biomedical applications of plant extracts.